Remote Testing of the Familiar Word Effect With Non-dialectal and Dialectal German-Learning 1–2-Year-Olds - Braun, Bettina; Czeke, Nathalie; Rimpler, Jasmin; Zinn, Claus; Probst, Jonas; Goldlücke, Bastian; Kretschmer, Julia; Zahner-Ritter, Katharina (Frontiers in Psychology, 2021)
Variability is pervasive in spoken language, in particular if one is exposed to two varieties of the same language (e.g., the standard variety and a dialect). Unlike in bilingual settings, standard and dialectal forms are often phonologically related, increasing the variability in word forms (e.g., German Fuß “foot” is produced as [fu<inline-graphic xlink:href="fpsyg-12-714363-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />s] in Standard German and as [f<inline-graphic xlink:href="fpsyg-12-714363-i002.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />s] in the Alemannic dialect). We investigate whether dialectal variability in children’s input affects their ability to recognize words in Standard German, testing non-dialectal vs. dialectal children. Non-dialectal children, who typically grow up in urban areas, mostly hear Standard German forms, and hence encounter little segmental variability in their input. Dialectal children in turn, who typically grow up in rural areas, hear both Standard German and dialectal forms, and are hence exposed to a large amount of variability in their input. We employ the familiar word paradigm for German children aged 12–18 months. Since dialectal children from rural areas are hard to recruit for laboratory studies, we programmed an App that allows all parents to test their children at home. Looking times to familiar vs. non-familiar words were analyzed using a semi-automatic procedure based on neural networks. Our results replicate the familiarity preference for non-dialectal German 12–18-month-old children (longer looking times to familiar words than vs. non-familiar words). Non-dialectal children in the same age range, on the other hand, showed a novelty preference. One explanation for the novelty preference in dialectal children may be more mature linguistic processing, caused by more variability of word forms in the input. This linguistic maturation hypothesis is addressed in Experiment 2, in which we tested older children (18–24-month-olds). These children, who are not exposed to dialectal forms, also showed a novelty preference. Taken together, our findings show that both dialectal and non-dialectal German children recognized the familiar Standard German word forms, but their looking pattern differed as a function of the variability in the input. Frequent exposure to both dialectal and Standard German word forms may hence have affected the nature of (prelexical and/or) lexical representations, leading to more mature processing capacities.